The Beginnings of the Church Career of Tomasz I, the Bishop of Wrocław, until Taking over the Office (1232) - Mieczysław Kogut (Wrocławski Przegląd Teologiczny)
Tomasz I descended from Jelenie-Jeleńczycy family line. His father Przybysław was a castellan in Sądowel and a lord in Powidzk. His uncle Piotr (died in 1240) was a provost of a cathedral chapter. Tomasz I did not complete his education at the level of a local cathedral school but started further studies at foreign universities, undoubtedly in Italy, accomplished by winning a doctorate. Owing to his uncle’s patronage, he became a member of a cathedral chapter. He also acted as a chancellor of Henryk Brodaty. The Bishop Tomasz I belongs to a group of those Polish bishops from the beginning of the 13th century who are known to had possessed holy orders at the moment of taking up the position of a diocesan bishop, which that time was not a common practice. He was elected the Bishop of Wroclaw in 1232. It can be stated with the substantial degree of probability that Tomasz was a candidate of the Silesian ruler – it is proved by the fact that immediately before consecration he had held an office of the chancellor of prince.